Das Verfahren vor dem Berner Kindes- und Erwachsenenschutzgericht - Hurni, Christoph (sui generis Verlag, 2020)
In the canton of Bern, the Child and Adult Protection Court performs the tasks of the judicial complaints authority in child and adult protection matters. It forms part of the civil department of the higher court and is made up of senior judges as well as specialist judges. The proceedings before this specialized court are characterized by a pluralism of legal sources: a federal rump order in the Swiss Civil Code is given concrete form by a cantonal special procedural code, which in turn refers to the general administrative process of the canton of Bern. The present work systematically presents the proceedings before the child and adult protection court and is intended to serve as an orientation for those seeking justice, lawyers and members of the court on procedural issues.